Ovarian pregnancy following fresh embryo transfer: A case report and literature review - Fombeno Kueta Pascal; Johnny El Hanna; Abdelilah Arsalane; Justin Lewis Denakpo (Case Reports in Women's Health)
Ovarian pregnancy is a rare and potentially life-threatening form of ectopic pregnancy, accounting for only 1.6 % to 2 % of all ectopic gestations. While its association with assisted reproductive technology is increasingly recognized, diagnosis remains challenging due to its nonspecific clinical and imaging features.This report concerns the case of a 29-year-old primigravida who presented with mild pelvic pain and vaginal spotting following a fresh embryo transfer. Transvaginal ultrasound revealed an empty uterus and a right ovarian mass. The patient had a serum β-hCG level of 3952 IU/L. Diagnostic laparoscopy indicated the presence of an ectopic pregnancy within the right ovary. Histopathological analysis of the excised mass confirmed the diagnosis. The patient recovered uneventfully following surgical management.Ovarian pregnancy following embryo transfer is an uncommon but serious complication of the use of assisted reproductive technology. Early diagnosis is crucial to prevent complications and preserve fertility.